USTANOWIENIE A UKONSTYTUOWANIE SIĘ POSAGU W RZYMSKIM PRAWIE KLASYCZNYM - Stępkowska, Agnieszka (Zeszyty Prawnicze, 2017)
On the Distinction between Assignment of the Dowry and its Constitution in Classical Roman Law Summary The dowry in Roman law (dos) was considered to be the husband’s property. Nevertheless its legal status was quite peculiar, when compared with the rest of the husband’s patrimony. The constitution of a dowry had a number of important legal consequences. Therefore it was crucial to indicate the moment of its establishment. The sole assignment of a dowry (dotis institutio) did not always have this effect. The reason for this was, that in classical Roman law there was a clear distinction between real and personal aspects of the property law. There were three ways for dotis institutio: dotis datio, dotis dictio, dotis promissio. In classical period only dotis datio had real effect and was the means by which - if done after marriage - dowry was immediately established. The other two were dowry agreements conferring on husband [or future husband] mere personal right to claim transfer of the patrimony subject to dictio or promissio. Therefore the dos took effect only after the husband became owner of the patrimony. In postclassical period this sharp distinction between assignment of a dowry and its material constitution gradually disappeared, and dotis institutio was considered to be only a real transfer of a property intended as a dowry. It was only Justinian who tried to restore this classical distinction. Nevertheless, acquiring the property subject to dotis institutio, although necessary, was not sufficient for dowry to take effect. The Roman dos derived its peculiar character from marriage. In case the transfer of patrimony dotis causa had taken effect before marriage (ante nuptias in dotem data) it acquired dotal character only after the marriage. If there was no marriage, the person assigning dowry (either woman, her pater familias, or a third person) was able to claim restitution of the patrimony intended previously to be dos, by means of condictio, or even by rei vindication in case the would-be husband did not acquired ownership, but only possession of the patrimony.